Epidemiological study of terbinafine‐resistant dermatophytes isolated from Japanese patients. Issue 4 (13th January 2021) - Hiruma, Junichiro; Noguchi, Hiromitsu; Hase, Midori; Tokuhisa, Yumie; Shimizu, Tatsuya; Ogawa, Takasuke; Hiruma, Masataro; Harada, Kazutoshi; Kano, Rui
Abstract: Terbinafine (TRF) has been used in the treatment of fungal infections for more than 20 years. Recently, TRF‐resistant Trichophyton interdigitale and T. rubrum strains have been isolated from human patients worldwide. However, an epidemiological study of TRF‐resistant strains in Japanese patients has not been investigated. In the present study, antifungal susceptibility testing was performed on clinical isolates from Japanese patients to assess TRF‐resistance patterns of T. interdigitale and T. rubrum strains. We also sequenced the squalene epoxidase ( SQLE ) encoding gene of TRF‐resistant T. rubrum strains. Two hundred and ten T. interdigitale and T. rubrum clinical isolates were obtained from 210 human cases of tinea pedis, tinea corporis, tinea unguium, tinea cruris, tinea manuum, tinea faciei and tinea capitis in Tokyo, Saitama, Chiba, Hyogo and Kumamoto, Japan, in 2020. Five T. rubrum isolates (N74, N79, N99, H30 and K2) grew on Sabouraud's dextrose agar (SDA) containing 1 mg/L of TRF. All five strains exhibited TRF minimum inhibitory concentrations (MICs) ≥32 mg/L but remained susceptible to azoles. We determined SQLE sequences in these TRF‐resistant T. rubrum strains and found that all strains harbored missense mutations (L393F) in the SQLE ‐encoding gene.